THE IMPORTANCE OF INTRAUTERINE DEVICES FOR THE REPRODUCTIVE HEALTH OF WOMEN OF CHILDBEARING AGE - Yusupova, U.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Intrauterine contraception (VMS): this device made of plastic with the addition of copper or other metals is considered one of the most effective abortive methods of pregnancy protection. In recent years, there have been significant improvements in the types and quality of such products. Hormonal contraception, presented by the IUD, reaches a reliability level of over 98%, surpassing traditional hormonal methods (about 10%). This advantage is due to: - High efficiency in preventing pregnancies; - The absence of systemic side effects for the woman’s body; Rapid restoration of reproductive function after removal of the IUD. Innovations and reduction of the risk of complications: the inclusion of copper, silver or gold in the composition significantly (2-9 times) minimizes the likelihood of inflammatory processes inside the uterus. This is achieved due to the antibacterial effect of metals.